Factors associated with mild cognitive impairment among elderly patients attending medical clinics in Universiti Kebangsaan Malaysia Medical Centre - Rosdinom Razali,; Azlin Baharudin,; Nik Ruszyanei Nik Jaafar,; Hatta Sidi,; Abdul Hadi Rosli,; Khoo, Boo Hooi; Lee, Tyan Shin; Noor Hafizah Samsudin Bahari,; Noralia Anis Elias, (Universiti Kebangsaan Malaysia, 2012)
Mild cognitive impairment (MCI) is a common condition among the elderly and is believed to be a precursor to Alzheimer disease. This study aims to detect the prevalence of MCI and factors associated with it. A cross-sectional study was conducted on a group of elderly patients attending various medical clinics in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) in 2010. Only patients aged 60 years and above, literate with no hearing or visual impairments were included. Screening instruments included the Mini Mental State Examination (MMSE) and a questionnaire on sociodemographic and clinical data. The cut-off points for MMSE for MCI was 21/30 to 28/30. The prevalence rate based on MMSE score for ‘normal’ and MCI were 35.3% and 64.7%, respectively. Most of the 346 patients (33.9%) had only one type of medical illness and on one type of medication. MCI was significantly associated with low educational achievement (p<0.05) and rheumatological diseases (p= 0.05). However, it is not associated with the number of medical illnesses suffered by patients and the number of medications prescribed. This study highlighted that MCI was a common condition among the elderly UKMMC Medical clinic attendees and was significantly associated with their low education level.